2014
DOI: 10.1111/jsap.12291
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective survey of ocular abnormalities in pugs: 130 cases

Abstract: The high number of cases of corneal pigmentation without keratoconjunctivitis sicca suggests that there may be additional yet undetermined factors involved in the development of corneal pigmentation in pugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
50
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(69 citation statements)
references
References 13 publications
7
50
2
1
Order By: Relevance
“…Lower eyelid distichia was overwhelmingly less prevalent than upper only or upper and lower eyelid distichiasis. These findings are also consistent with previous reports …”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Lower eyelid distichia was overwhelmingly less prevalent than upper only or upper and lower eyelid distichiasis. These findings are also consistent with previous reports …”
Section: Discussionsupporting
confidence: 94%
“…The breed and age distribution of patients in this study are similar to previous reports of distichiasis in dogs, and English Bulldogs were overrepresented. Females were more commonly affected (63%) than males (37%) in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…16 The distribution of KP-HED in these three breeds were specific among each breed and different as compared to KP-HED described in other small-sized dog breeds. 17 Three of the five most common KP-HED found in these breeds (i.e., 'cataract', 'keratoconjunctivitis sicca', 'retinal dysplasia, geographic or detached forms') are listed in the current list of the ACVO as 'disorders for which there is an unequivocal recommendation against breeding in all breeds'. 10 The first most common KP-HED in the population was the cataract.…”
Section: Discussionmentioning
confidence: 99%
“…Primary causes of CUD in dogs include spontaneous chronic corneal ulceration (SCCED) [5, 10, 16] and canine herpes virus-1 [17]. Multiple secondary causes are reported, including entropion [18, 19], ectopic cilia [8, 20], primary and secondary forms of keratoconjunctivitis sicca (KCS) [7, 21], corneal degeneration [22], traumatic events [23–25], corneal overexposure related to general anesthesia [26], facial nerve paralysis [27] and orbital diseases [28, 29]. Many of these factors have also been associated with certain breed phenotypes [30] and some smaller studies based on referral populations of less than 250 cases have reported increased CUD prevalence in breed-types such as brachycephalic [7, 31, 32] or spaniel types [7, 33].…”
Section: Introductionmentioning
confidence: 99%